2021
DOI: 10.3390/pathogens10060677
|View full text |Cite
|
Sign up to set email alerts
|

Association between Toxoplasma gondii Exposure and Suicidal Behavior in Patients Attending Primary Health Care Clinics

Abstract: This study aimed to determine the association between suicidal behavior and T. gondii seroreactivity in 2045 patients attending primary care clinics. IgG antibodies against T. gondii were found in 37 (12.1%) out of 306 individuals with a history of suicidal ideation and in 134 (7.7%) of 1739 individuals without this history (OR: 1.64; 95% CI: 1.11–2.42; p = 0.01). Seropositivity to T. gondii was associated with suicidal ideation in women (OR: 1.56; 95% CI: 1.01–2.42; p = 0.03) and individuals aged ≤30 years (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The results of our study may mean that infection with T. gondii could lead to sexual promiscuity, especially in men, or that people with sexual promiscuity could have risk factors that favor infection with T. gondii. Sexual promiscuity has been linked to mental health problems in men [43], and infection with T. gondii has been linked to mental disorders [10][11][12][13][14][15]. Therefore, sexual promiscuity might be a manifestation of mental disorders in some individuals exposed to T. gondii.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of our study may mean that infection with T. gondii could lead to sexual promiscuity, especially in men, or that people with sexual promiscuity could have risk factors that favor infection with T. gondii. Sexual promiscuity has been linked to mental health problems in men [43], and infection with T. gondii has been linked to mental disorders [10][11][12][13][14][15]. Therefore, sexual promiscuity might be a manifestation of mental disorders in some individuals exposed to T. gondii.…”
Section: Discussionmentioning
confidence: 99%
“…T. gondii can persist lifelong in the central nervous system within neurons, modifying their function and structure and leading to specific behavioral changes of the host [9]. Infections with T. gondii have been associated with schizophrenia [10,11], suicide behavior [12][13][14], mixed anxiety and depressive disorder [15], traffic accidents [16], and aggression [17]. In contrast, some studies have shown a lack of association between T. gondii seropositivity and depression in pregnant women [18], completed suicide [19], and bipolar disorder [20].…”
Section: Introductionmentioning
confidence: 99%
“…It is unknown whether decedents included in the control group had had suicidal behavior in life. Recent studies in Mexico have shown an association between T. gondii seropositivity and suicidal behavior in several population groups including patients attending primary health care clinics [ 26 ] and people with alcohol consumption [ 27 ]. Further studies including a wide range of sociodemographic, clinical, and behavioral variables to determine the association between T. gondii infection and suicide should be conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic toxoplasmosis might be responsible for a vast array of neuropsychiatric symptoms [9]. Seroprevalence of T. gondii infection has been linked to mixed anxiety and depressive disorder [10], schizophrenia [11, 12], depression [13, 14], and suicide behavior [14-15]. Few studies have shown a link between T. gondii infection and insomnia.…”
Section: Introductionmentioning
confidence: 99%